Agrikit - Nasni Naseri, Roszi Naszariah; Hussin, Harniyati (Universiti Teknologi MARA Cawangan Johor Kampus Pasir Gudang, 2025)
In 2014, the Federal Agricultural Marketing Authority (FAMA) developed AgroBazaar Online to help smallholder farmers in Malaysia market their products. This platform specifically focuses on agricultural products; however, it remains underutilized by rural farming communities. To address this gap, AGRIKIT was developed as a user-friendly physical training solution tailored for smallholder farmers. AGRIKIT includes a physical book featuring visual guides, infographic instructions, and simplified language to make the learning process straightforward and accessible. The kit simplifies e-commerce adoption by covering essential steps such as registering an account, setting up a profile, managing and listing products for sale, and tracking orders and payments. Its user-centric design ensures accessibility for individuals with limited technical skills. By empowering farmers to connect directly with markets, AGRIKIT reduces dependency on intermediaries, fosters digital inclusion, and promotes sustainable farming practices. With scalability potential across ASEAN countries, AGRIKIT offers strong commercialization opportunities through strategic partnerships.